2007
DOI: 10.1177/107769900708400308
|View full text |Cite
|
Sign up to set email alerts
|

Male Body Image and Magazine Standards: Considering Dimensions of Age and Ethnicity

Abstract: This study contributes to two theory streams by examining magazine use among males, along dimensions of age and ethnicity. First, social comparison theory (SCT) is invoked to examine how males use magazine images to benchmark the "ideal" male. Second, a developing theory of magazines as standard bearers for "the ideal woman" is modified to suggest that magazines also set standards for "the ideal man.'' Findings of focus groups and interviews with two generations of males -Generation X and Baby Boomers (BBs)-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 1 publication
2
14
1
1
Order By: Relevance
“…The study showed that men who read fitness magazines were more likely than women to internalise the ideals of the muscular bodies on display, and that this could explain eating problems and body‐shape dissatisfaction in men. Similar research concluded that viewing men's magazines could have a negative effect on men's self‐esteem in relation to their bodies (Botta, ; Duggan & McCreary, ; Farquhar & Wasylkiw, ; Hatoum & Belle, ; Hobza, Walker, Yakushko, & Peugh, ; Johnson, McCreary, & Mills, ; Morrison, Kalin, & Morrison, ; Morrison, Morrison, & Hopkins, ; Parasecoli, ; Pompper, Soto, & Piel, ).…”
Section: Thematics Of Masculinitymentioning
confidence: 89%
“…The study showed that men who read fitness magazines were more likely than women to internalise the ideals of the muscular bodies on display, and that this could explain eating problems and body‐shape dissatisfaction in men. Similar research concluded that viewing men's magazines could have a negative effect on men's self‐esteem in relation to their bodies (Botta, ; Duggan & McCreary, ; Farquhar & Wasylkiw, ; Hatoum & Belle, ; Hobza, Walker, Yakushko, & Peugh, ; Johnson, McCreary, & Mills, ; Morrison, Kalin, & Morrison, ; Morrison, Morrison, & Hopkins, ; Parasecoli, ; Pompper, Soto, & Piel, ).…”
Section: Thematics Of Masculinitymentioning
confidence: 89%
“…Media representations of an ideal man's body have increased in frequency (Ricciardelli, Clow, & White, 2010), stimulating men's desire to replicate these body types (Brennan, Crath, Hart, Gadalla, & Gillis, 2011;Pompper, Soto, & Piel, 2007). Corroborating Van der Mast's (2010) results, images of slender, muscular male bodies generate increased men's body dissatisfaction (Galioto & Crowther 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Because thin-ideal internalization is fostered by perceived pressure to be thin (Boone, Soenens, & Braet, 2011), individuals will be more likely to experience body image dissatisfaction when encountering stressful messages (Jones, Vigfusdottir, & Lee, 2004). Furthermore, the pressure to be thin can come from social comparisons, such as family, peers or the entire collectivity (Fitzsimmons-Craft, Harney, Koehler, Danzi, Riddell, & Bardone-Cone, 2012;Pompper, Soto, & Piel, 2007). Morrison et al (2012) further indicate that general social comparison is significantly associated with body image dissatisfaction among college women.…”
Section: Cultural Differences On Body Image Dissatisfaction: the Socimentioning
confidence: 99%